Efficacy of the multimodal strategy for Hand Hygiene compliance: an integrative review - Marília Duarte Valim; Ianne Lanna de Souza Rocha; Thais Pedroso Martins Souza; Yasmin Aparecida da Cruz; Thaissa Blanco Bezerra; Érica Baggio; Richarlisson Borges de Morais; Antônio César Ribeiro (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: Evaluate, from the literature, the effectiveness of the implementation of the multimodal strategy for health professionals compliance with Hand Hygiene and its sustainability over time. Method: Integrative review, with a view to answering the following question: "Is the implementation of the multimodal strategy effective in health professionals compliance with Hand Hygiene and can it be sustained over time?". The MEDLINE, SCOPUS, LILACS and CINAHL databases were used to retrieve the primary articles. Results: Twenty-five studies were analyzed. Among the components of the multimodal strategy, three need to be better worked: health education, feedback from practices and management involvement. Although it needs to focus more on its five elements, interventions based on the multimodal strategy have favored HH compliance and its long-term sustainability. Conclusion: The strategy proved to be effective for HH compliance, especially when all integrating components are adequately addressed.